PERSEPSI MAHASISWA DAN DOSEN TERHADAP MODEL PEMBELAJARAN BAHASA ARAB INTERAKTIF BERBASIS PLATFORM NON-ARABS.COM: STUDENT AND LECTURER PERCEPTION OF THE INTERACTIVE ARABIC LANGUAGE LEARNING MODEL BASED ON THE NON-ARABS.COM PLATFORM - Yurianto, Ramdhan; Karimah, Lina Husnul; Mubarokah , Nida Farhani (Lisanul Arab: Journal of Arabic Learning and Teaching, 2025)
In this era of educational technology, learning platforms have played a very important role in the educational process. Learning that was previously teacher-centered (teacher-centered) has now been slowly abandoned and began to change to student-centered. Interactive Learning is influenced by several things, one of which is the existence of an Interactive platform. With the existence of this Interactive learning platform, it is finally for students to be active, creative, and willing to interact with the platform itself. Not limited to certain courses, learning platforms have emerged to support any learning with the function of increasing motivation in learning and improving student learning outcomes, including Interactive learning platforms in Arabic courses. This platform that has supported the learning of Arabic language skills, such as listening, speaking, reading and writing skills is perfect for research. This study wants to further examine one of the Interactive platforms in language lectures that has been designed and ready to use without having to prepare their own material, besides that the researcher also wants to examine the effectiveness of this non-arab.com platform and explore the perception of lecturers and students about it. This research is a field research with observation data collection methods, interviews and documentation.